Petik Laut Tradition as Preservation of Local Culture: A Living Qur'an Study in Kranji Village, Paciran, Lamongan - Fahimah, Siti; Joeha, Avif Alfiyah (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
This research contains a study of the tradition of sea harvesting that has been carried out for decades by the residents of Kranji Paciran Lamongan village. The activity is conducted once a year, every August, coinciding with the celebration of the Independence Day of the Republic of Indonesia. This study uses a qualitative method and is presented descriptively using the living al-Qur'an approach. Data collection is done through observation and interviews related to the al-Qur'an values that underlie the activity and its institutionalization as a religious tradition preserved by the community. The research findings indicate that the tradition is based on the values of gratitude taught by religion, as expressed in the al-Qur'an. The gratitude referred to is the thankfulness for the abundance of blessings in the form of marine resources. It also includes gratitude as an expression of thanks to the ancestors. The series of activities within the tradition is a blend of Islamic elements, such as religious lectures, and Javanese culture, in the form of a shadow puppetry (wayang kulit) performance. Through these activities, it is hoped that the community of Kranji village, especially the fishing families, will become more prosperous, secure, and be protected from dangers, including malevolent spirits. The religious values within the tradition are packaged in the form of collective remembrance (zikir) to strengthen faith in Allah. Meanwhile, the timing of the organization, coinciding with the commemoration of Independence Day, is an effort to preserve and foster a spirit of love for the homeland.